2004
DOI: 10.1038/sj.onc.1207700
|View full text |Cite|
|
Sign up to set email alerts
|

The topoisomerase I- and p53-binding protein topors is differentially expressed in normal and malignant human tissues and may function as a tumor suppressor

Abstract: Topors was identified recently as a human protein that binds to topoisomerase I and p53. Topors contains a highly conserved RING domain and localizes in promyelocytic leukemia nuclear bodies. Relatively little is known regarding topors expression patterns or function. We now demonstrate that topors mRNA and protein are widely expressed in normal human tissues. By contrast, topors mRNA and protein levels are decreased or undetectable in colon adenocarcinomas relative to normal colon tissue, and expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 26 publications
(36 reference statements)
1
45
1
Order By: Relevance
“…Therefore, topors could affect the stability of p53 via covalent modification of p53 by ubiquitin isopeptide. This observation, however, is not necessarily consistent with our and others' previous observations suggesting topors as a likely tumor suppressor protein since polyubiquitination of p53 mediated by GFPtopors induces proteasome-dependent downregulation of p53 in U2-OS cells (Chu et al, 2001;Rajendra et al, 2004;Saleem et al, 2004). This implies that regulation of p53 by topors may involve not only ubiquitination but also some other molecular mechanism.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Therefore, topors could affect the stability of p53 via covalent modification of p53 by ubiquitin isopeptide. This observation, however, is not necessarily consistent with our and others' previous observations suggesting topors as a likely tumor suppressor protein since polyubiquitination of p53 mediated by GFPtopors induces proteasome-dependent downregulation of p53 in U2-OS cells (Chu et al, 2001;Rajendra et al, 2004;Saleem et al, 2004). This implies that regulation of p53 by topors may involve not only ubiquitination but also some other molecular mechanism.…”
Section: Discussioncontrasting
confidence: 52%
“…While this manuscript was in preparation, Saleem et al (2004) also reported that transient expression of h-topors showed antiproliferative activity and was associated with G0/G1 cell cycle arrest in HeLa cells. Our results additionally show that overexpression of topors could activate the expression of p53 and induce either cell cycle arrest or apoptotic response.…”
Section: Discussionmentioning
confidence: 99%
“…However, TOPORS maps to chromosome 9p21 and is located between microsatellite markers D9S270 and D9S273, which show loss of heterozygosity in 21.8 and 13.8% of prostate cancer samples examined, respectively (37). In addition, TOPORS protein has been shown to be diminished in colon cancer, where it may have tumor suppressor function (24). TOPORS has also been implicated as a tumor suppressor in human gliomas and non-small cell lung cancers (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase I is thought to interact with the RING domain-containing protein TOPORS (21), which is known to interact with the tumor suppressor p53 (22) and later was found to ubiquitinate p53 (23). TOPORS is widely expressed in various tissues including the prostate (24 …”
mentioning
confidence: 99%
“…These include UGT1A1 and HNF1, which are involved in irinotecan elimination and display increased expression in irinotecan-resistant cell lines [Gagnon et al 2006;BĆ©langer et al 2010], TOPORS, which is involved in topoisomerase I and p53-binding [Saleem et al 2004], and DEXI, which is hypermethylated and showed demethylation with improved response to irinotecan after DAC treatment [Miyaki et al 2012]. Conversely, there was decreased sensitivity to irinotecan when DEXI was silenced with siRNA [Miyaki et al 2012].…”
Section: Chemosensitizationmentioning
confidence: 99%